Secular trends in growth in the high‐altitude district of Nuñoa, Peru 1964–2015. Issue 1 (21st November 2018) - Hoke, Morgan K.; Leatherman, Thomas L.
Abstract: Objectives: Nuñoa, Peru has been the site of anthropological research on human adaptability, growth, and health since the 1960s. Previous studies documented a nascent secular trend in growth between 1964 and 1984. However, no secular trend was evident when the population was re‐examined in 1999, following an intervening period of sociopolitical upheaval. Subsequently, the region experienced considerable economic development reflected in secular increases in height. We seek to evaluate trends in growth and BMI among Nuñoan children over 50 years. Materials and methods: Anthropometric data for 929 children collected in 2015 are compared with anthropometric data for 394 children from 1964, 912 children from 1984, and 292 children from 1999. The data were converted to z ‐scores using the WHO 2007 growth standards. anova is used to evaluate rates of stunting, underweight, overweight, and obesity across the study periods. Results: We observe small increases in stature and weight between the 1960s and 1980s, almost no change between the 1980s and 1990s and statistically significant reductions in stunting and increases in height between the 1990s and 2015. Discussion: There were relatively small differences in stature and weight and a high incidence of stunting between 1964 and 1999 attributed to extremely poor economic and health conditions. A large secular increase in height (7–8 cm on average) and consequent reduction in rates of stunting between 1999 and 2015 occurred due to improved social and economic conditions. In addition to political stabilization, enhanced infrastructure, social aid programs, improved healthcare, and economic expansion contribute to these trends.